Pengembangan Life Skill Perempuan dalam Kriya Tekstil Makrame - Rahayu, Poppy; Husniadhy, Annisya Pramesti; Dwi, Aulia; Fauziah, Syifa (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2021)
In general, housewives have a lot of free time that can be used for more effective activities. For this reason, it is necessary to strive for an activity that can be carried out by housewives that have economic value to provide additional family income. This community service activity aimed to improve skills of textile crafts for housewives who are members of the Integrated Entrepreneurship Development community. These skills are a provision for entrepreneurship so that members can have craft products and can market the results of the macrame crafts through an online shop. The service activity was carried out to facilitate housewives who have a strong desire to be able to help the family economy. The activity used the lecture method, learning by doing, and discussion. This training was guided by makrame craftsmen with the assistance of the committee. The service activity was carried out at the East Jakarta Creative Gathering Place. The result of this activity was that participants could make makrame bags and understand the marketing process through the online shop. This training received a positive response and assessment from the participants.Â